Using intervention mapping to design a self‐management programme for older people with chronic conditions. Issue 1 (17th October 2018) - Burrell, Beverley; Jordan, Jennifer; Crowe, Marie; Wilkinson, Amanda; Jones, Virginia; Harris, Shirley; Gillon, Deborah
Abstract: Self‐management programmes provide strategies to optimise health while educating and providing resources for living with enduring illnesses. The current paper describes the development of a community‐based programme that combines a transdiagnostic approach to self‐management with mindfulness to enhance psychological coping for older people with long‐term multimorbidity. The six steps of intervention mapping (IM) were used to develop the programme. From a needs assessment, the objectives of the programme were formulated; the theoretical underpinnings then aligned to the objectives, which informed programme design, decisions on implementation, programme adoption and evaluation steps. Bandura's social cognitive theory informed the methods and practical strategies of delivery. Among the features addressed with participants are transdiagnostic dimensions such as fatigue, pain, breathlessness, sleep disturbances. The programme utilises mindfulness to aid coping and ameliorate the psychological distresses associated with chronicity. Findings from an initial feasibility study and subsequent pilot assisted in conceptualising our programme. In conclusion, applying IM gave the planners confidence the programme is robust and evidence‐based with clearly articulated links between the behavioural goals and design elements to obtain the desired outcomes.